HNF-4α regulates expression of human ornithin carbamoyltransferase through interaction with two positive cis-acting regulatory elements located in the proximal promoter - Lukšan, O; Dvořáková, L; Jirsa, M (Folia biologica, 2014)
OTC encodes ornithine carbamoyltransferase, mitochondrial matrix enzyme involved in the synthesis of urea. The tissue-specific expression of OTC in the liver and intestine is dependent on the interaction of OTC promoter with an upstream enhancer. HNF-4 and C/EBPβ are crucial for this interaction in the rat and mouse. In the present study we focused on characterization of elements involved in the regulation of OTC transcription in human. Using a set of 5'-deleted promoter mutants in a reporter assay we identified two positive cis-acting regulatory elements located at c.-105 and c.-136 within the human OTC promoter. Both are essential for the transcriptional activity of the promoter itself and for the interaction with the enhancer. Protein binding at the corresponding sites was confirmed by DNase I footprinting. Electromobility shift assay with a specific competitor and anti-HNF-4α antibody identified the DNA-protein binding sites as HNF-4α recognition motifs. A third HNF-4α binding site has been found at the position c.-187. All three HNF-4α binding sites are located within 35 bp upstream of the transcription start sites at positions c.-95, c.-119 (major) and c.-169 (minor). A series of C/EBPβ recognition motifs was identified within the enhancer. Involvement of C/EBPβ and HNF-4α in the promoter-enhancer interaction is further supported by a massive DNAprotein interaction observed in the footprinting and EMSA assays. Since the OTC promoter lacks general core promoter elements such as TATA-box or initiators in standard positions, HNF-4α most likely plays an essential role in the initiation of OTC transcription in human.
Keywords: mutace; hepatocytární jaderný faktor 4; Animals; 5' Flanking Region; Gene Expression Regulation, Enzymologic; Base Sequence; Hep G2 Cells; regulace genové exprese enzymů; buňky Hep G2; DNA footprinting; počítačová simulace; luciferasy; retardační test; vazba proteinů; reportérové geny; Transcription, Genetic; DNA; lidé; Molecular Sequence Data; Mice; Mutation; Protein Binding; myši; ornithinkarbamoyltransferasa; Computer Simulation; DNA Footprinting; Deoxyribonuclease I; genetická transkripce; Ornithine Carbamoyltransferase; molekulární sekvence - údaje; Sequence Alignment; Luciferases; sekvence nukleotidů; krysa rodu Rattus; deoxyribonukleasa I; promotorové oblasti (genetika); zvířata; Genes, Reporter; Promoter Regions, Genetic; 5' přiléhající oblast DNA; Electrophoretic Mobility Shift Assay; Hepatocyte Nuclear Factor 4; Rats; sekvenční seřazení; Humans